Characterization of mortality in children with sickle cell disease diagnosed through the Newborn Screening Program - Alessandra P. Sabarense; Gabriella O. Lima; Lívia M.L. Silva; Marcos Borato Viana (Elsevier, 2015)
Objective: To characterize the deaths of 193 children with sickle cell disease screened by a neonatal program from 1998 to 2012 and contrast the initial years with the final years. Methods: Deaths were identified by active surveillance of children absent to scheduled appointments in Blood Bank Clinical Centers (Hemominas). Clinical and epidemiological data came from death certificates, neonatal screening database, medical records, and family interviews. Results: Between 1998 and 2012, 3,617,919 children were screened and 2,591 had sickle cell disease (1:1,400). There were 193 deaths (7.4%): 153 with SS/Sβ0-talassemia, 34 SC and 6 Sβ+thalassemia; 76.7% were younger than five years; 78% died in the hospital and 21% at home or in transit. The main causes of death were infection (45%), indeterminate (28%), and acute splenic sequestration (14%). In 46% of death certificates, the term "sickle cell" was not recorded. Seven-year death rate for children born between 1998 and 2005 was 5.43% versus 5.12% for those born between 2005 and 2012 (p = 0.72). Medical care was provided to 75% of children; 24% were unassisted. Medical care was provided within 6 hours of symptom onset in only half of the interviewed cases. In 40.5% of cases, death occurred within the first 24 hours. Low family income was recorded in 90% of cases, and illiteracy in 5%. Conclusions: Although comprehensive and effective, neonatal screening for sickle cell disease was not sufficient to significantly reduce mortality in a newborn screening program. Economic and social development and increase of the knowledge on sickle cell disease among health professionals and family are needed to overcome excessive mortality. Resumo: Objetivo: Caracterizar os 193 óbitos de crianças com doença falciforme diagnosticadas por programa de triagem neonatal entre 1998-2012 e comparar os primeiros com os últimos anos. Métodos: Os óbitos foram identificados pela busca ativa das crianças ausentes nas consultas agendadas nos hemocentros. Dados clínicos e epidemiológicos provieram dos documentos de óbito, banco de dados da triagem neonatal, prontuários médicos e entrevistas com familiares. Resultados: Entre 1998-2012 foram triadas 3.617.919 crianças, 2.591 com doença falciforme (1:1.400). Ocorreram 193 óbitos (7,4%): 153 com SS/Sβ0-talassemia, 34 SC e 6 Sβ+-talassemia; 76,7% em crianças com menos de 5 anos; 78% faleceram em hospitais e 21% em domicílio ou trânsito. Causas principais do óbito: 45% infecção, 28% indeterminada, 14% sequestro esplênico agudo. Em 46% dos documentos de óbito, não houve registro do termo "falciforme". A taxa de mortalidade até sete anos das crianças nascidas entre 1998-2005 foi 5,43% versus 5,12%, entre 2005-2012 (p=0,72). Receberam assistência médica 75% das crianças; 24% ficaram desassistidas. Pelas entrevistas, atendimento médico teria ocorrido nas primeiras seis horas do início dos sintomas em metade dos casos. O óbito ocorreu em 40,5% dos casos, nas primeiras 24 horas. Baixa renda familiar foi registrada em 90% dos casos e analfabetismo em 5%. Conclusões: A triagem para doença falciforme, mesmo abrangente e eficaz, não foi suficiente para reduzir significativamente a mortalidade no Programa de Triagem Neonatal. Necessita-se de desenvolvimento econômico e social do estado e ampliação, pela educação continuada, do conhecimento sobre a doença falciforme entre os profissionais de saúde e familiares. Keywords: Sickle cell anemia, Death rate, Infection, Acute splenic sequestration, Neonatal screening, Palavras-chave: Anemia falciforme, Mortalidade, Infecção, Sequestro esplênico agudo, Triagem neonatal